The orientalism of Mary Wollstonecraft under Nawal el Saadawi: a cross cultural dialogue - Bonfim, Sarah; Luz, Flávia Abud (Malala, 2022)
There is a contradiction that prevents the reading of Mary Wollstonecraft’s Vindication of the Rights of Women (1792) from flowing as liberty project: her positions regarding the Muslim Turkish people, especially women from this group. In this article, our proposal is to present a contribution to this debate, based on excerpts from the book that touch on two points considered fundamental in our analysis: the cultural issue of the harem and the religious issue about the denial of an immortal soul to Muslim women. Therefore, we resorted to the work of Nawal El Saadawi, keeping in mind two important perspectives, specifically, Grada Kilomba’s concept of Otherness and Abdullah An-Na’im’s concept of intercultural dialogue. In this sense, our objective is to contribute to the reflection on the prejudices repeated in Wollstonecraft’s work. We seek to reflect on the aspects without disregarding the philosopher’s other contributions to the political philosophy history.